The Mechanisms of Peripheral Nerve Preconditioning Injury on Promoting Axonal Regeneration - Xiaoyan Yang; Ruixuan Liu; Ying Xu; XiangYu Ma; Bing Zhou (Neural Plasticity)
Two major factors contribute to the failure of axonal regrowth in the central nervous system (CNS), namely, the neuronal intrinsic regenerative capacity and the extrinsic local inhibitory microenvironments. However, a preconditioning peripheral nerve lesion could substantially enhance the regeneration of central axons following a subsequent spinal cord injury. In the present review, we summarize the molecular mechanisms of the preconditioning injury effect on promoting axonal regeneration. The injury signal transduction resulting from preconditioning peripheral nerve injury regulates the RAG expression to enhance axonal regeneration. Importantly, preconditioning peripheral nerve injury triggers interactions between neurons and nonneuronal cells to amplify and maintain their effects. Additionally, the preconditioning injury impacts mitochondria, protein, and lipid synthesis. All these coordinated changes endow axonal regeneration.